If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = 4(2y + -7) Reorder the terms: 2 + 3y = 4(2y + -7) Reorder the terms: 2 + 3y = 4(-7 + 2y) 2 + 3y = (-7 * 4 + 2y * 4) 2 + 3y = (-28 + 8y) Solving 2 + 3y = -28 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 2 + 3y + -8y = -28 + 8y + -8y Combine like terms: 3y + -8y = -5y 2 + -5y = -28 + 8y + -8y Combine like terms: 8y + -8y = 0 2 + -5y = -28 + 0 2 + -5y = -28 Add '-2' to each side of the equation. 2 + -2 + -5y = -28 + -2 Combine like terms: 2 + -2 = 0 0 + -5y = -28 + -2 -5y = -28 + -2 Combine like terms: -28 + -2 = -30 -5y = -30 Divide each side by '-5'. y = 6 Simplifying y = 6
| 2*8+8y=16 | | 4x-5=2y-7 | | 2y-7=3y-12 | | 3u-8=16 | | 2(u-13)=4(16-4) | | z^4+2z^3+z+2=0 | | B(4b-3)=0 | | (9/10)x=45 | | 3v-4=11 | | 4.3v-4=11 | | 2p+5p-3=0 | | -2/n-6-6/2n+3 | | 2u-10=6 | | 5x+9x=-111-7x | | 3x=8x-36 | | m^2+4m-17=-3 | | 8v+40=2(3v+10)-1 | | 6(3(-2)-1)=-42 | | 2r^3+16r^2=0 | | 6.3=h-20 | | (2R-13)-(-6R+4)= | | 42-x+3=20 | | 4x-16=-x-1 | | 3/4(8p+1)+3/8(16p-8) | | 34=28-2/5x | | 10x+9=5x-21 | | n^2+12n-33=-10 | | 3(5x-6)=2(x+3) | | 10a^2-100a=0 | | -3/8x+41=-22 | | 4*(b-3)=b-27 | | 2x-12=0x-6 |